In Vitro Assembly of Sindbis Virus Core-Like Particles from Cross-Linked Dimers of Truncated and Mutant Capsid Proteins - Tellinghuisen, Timothy L. (American Society for Microbiology, 2001)
A nucleic acid-bound capsid protein dimer was previously identified using a Sindbis virus in vitro nucleocapsid assembly system and cross-linking reagents. Cross-link mapping, in combination with a model of the nucleocapsid core, suggested that this dimer contained one monomer from each of two adjacent capsomeres. This intercapsomere dimer is believed to be the initial intermediate in the nucleocapsid core assembly mechanism. This paper presents the purification of cross-linked dimers of a truncated capsid protein and the partial purification of cross-linked dimers of a full-length assembly-defective mutant. The assembly of core-like particles from these cross-linked capsid protein dimers is demonstrated. Core-like particles generated from cross-linked full-length mutant CP(19-264)L52D were examined by electron microscopy and appeared to have a morphology similar to that of wild-type in vitro-assembled core-like particles, although a slight size difference was often visible. Truncated cross-linked CP(81-264) dimers generated core-like particles as well. These core-like particles could subsequently be disassembled when reversible cross-linking reagents were used to form the dimers. The ability of the covalent intercapsomere cross-link to rescue capsid proteins with assembly defects or truncations in the amino-terminal region of the capsid protein supports the previous model of assembly and suggests a possible role for the amino-terminal region of the protein.